(untitled) (Research, Society and Development, 2021)
The management process is present in different economic sectors and allows for more assertive decision-making with better results. This process is endowed with best practices and methods that facilitate the triggering of the entire organizational structure regarding activities and deliverables. In civil construction, the development of new technologies, market demands, and organizational challenges in the pursuit of excellence has led companies to rethink their management systems. The objective of this work is to identify the best practices and tools used in construction sites in Brazil, based on the perception of civil construction professionals, contractors, and other companies related to the sector. The methodology used is based on a bibliographic study through academic works in order to support the study, as well as field research with market professionals at different levels and positions. The results showed negligence in several aspects, including legal, for the project development and construction site planning. It also showed negligence in the planning phase, and the culture of immediacy and improvisation, in addition to pressure for the production stage and cost reduction. It was possible to verify the lack of adoption of proper and effective guidelines and methodology. Finally, it was contacted, even so, that good practices have been used in the construction sites, from simple tools to the application of more modern systems and the use of innovative technologies, and that the planning and design process of the construction site can bring greater productivity, reduction of waste and quality improvement in Civil Construction.